Tahapan Pengajaran Bilingual dalam Konteks Kurikulum Merdeka: Studi Literatur untuk Sekolah Dasar - F, Faiqussabila; Janah, Dyah Nur Hidayatun; Nabila, Nadya Marell; Meganesia, Vinardita; Pebrian, Melina; Maharani, Putri; Widagdo, Arif (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Bilingual learning is an educational approach that integrates two languages in the learning process to improve students’ language skills as well as understanding of academic materials. This study discusses the stages of implementing bilingual learning, its suitability to the Independent Curriculum, and literature studies that support its effectiveness. The learning stages start from introducing vocabulary contextually to developing conversation skills through interactive activities. The Independent Curriculum, which emphasizes differentiated and student-centered learning, provides a strong foundation for the implementation of bilingual learning. The results of the literature study show that the success of bilingual learning is influenced by teacher readiness, support for facilities and infrastructure, and parental involvement. Despite a number of challenges, bilingual learning has great potential in equipping students with the language competencies needed in the era of globalization. Therefore, ongoing support from all parties is needed to optimize its implementation in elementary schools.